INFLUENCE OF TEACHERS’ INNOVATION AND CREATIVITY ON STUDENTS’ OUTCOMES IN PUBLIC SECONDARY SCHOOLS IN HAMISI SUB- COUNTY, KENYA - Opondo, Gabriel Okolla; Amunga, Jane (IJRDO- Journal of Educational Research, 2023)
The purpose of this study was to investigate the influence of teachers’ innovation and creativity on students’ outcomes in public secondary schools in Hamisi Sub- County, Kenya . This study encompassed a total of 8,662 participants, including 52 principals, 511 teachers employed by the Teachers Service Commission (TSC), 8,095 Form Four students, and 4 curriculum support officers, all representing the target population. To obtain the sample size, a simple random  and stratified sampling technique was applied, guided by the Krejcie and Morgan table (1970), resulting in a sample of 368 respondents, consisting of 22 principals, 22 teachers, and 340 students. The selection of the 4 curriculum support officers was done purposefully to ensure their participation in the study. This study was grounded in Bandura's social learning theory. The secondary schools and participants involved in the pilot study were not part of the primary investigation; their role was solely to enhance and refine the data collection instruments. Data analysis was carried out using descriptive statistics, including frequencies and percentages, as well as inferential statistics. The study findings were presented using tables, graphs, and charts. The findings emphasized the significant impact of teachers' perceptions and attitudes on the academic outcomes of students in the Hamisi Sub-County, Kenya. Teachers who prioritized students' success, positively contributed to academic achievement, and demonstrated a commitment to improving outcomes contributed to a favourable learning environment. Effective time management practices, encompassing thorough curriculum coverage and prudent allocation of teaching time, significantly influenced students' educational experiences. Additionally, the study highlighted the pivotal role of teachers' innovation and creativity, emphasizing engaging teaching methods, encouragement of creative thinking, and adaptable approaches. Furthermore, academic clinics, providing academic support beyond regular hours, positively impacted academic consultations and enhanced student behaviour. In conclusion, teachers in Hamisi Sub-County, Kenya, exerted substantial influence on students' academic performance and experiences, driven by their attitudes, time management, innovation, and academic support. Recommendations include comprehensive teacher training, emphasis on positive attitudes and effective time management, fostering innovation in teaching, establishing monitoring and evaluation systems, curriculum enhancements for creativity, and promoting parent-teacher engagement through workshops, all aimed at improving student outcomes and fostering a dynamic learning environment.